Human–Animal Interaction: A Concept Analysis. Issue 1 (25th September 2012) - Vitztum, Coley
Abstract : PURPOSE: A concept analysis was performed on human–animal interaction (HAI). DATA SOURCE: Nursing, psychology, and behavioral sciences literature. DATA SYNTHESIS: Uses and definitions associated with HAI were used to articulate the attributes, antecedents, consequences, and empirical referents. Model, borderline, and contrary cases were developed. CONCLUSIONS: HAI is operationally defined. IMPLICATIONS FOR NURSING PRACTICE: Including HAI as a health promotion behavior, within a theoretical framework, appears to be a promising intervention and may be linked to physical activity.